The growth rate of Nile tilapia Oreochromis niloticus fry fed on fermented Lemna sp. meal - Rita Rostika; Yuli Andriani; Arthur Henry Abram; Apriana Vinasyiam (Jurnal Akuakultur Indonesia, 2017)
ABSTRACT